57. Botulinum toxin type-A therapy in cluster headache: Two clinical cases. Issue 12 (December 2016) - Cesaretti, C.; Cesaris, F. De; Amantini, A.; Lori, S.
Abstract : Cluster headache (CH) is a primary chronic disabling form with autonomic symptoms, that often does not respond satysfactorily to prophylactic treatment. Botulinum toxin type A is an effective therapy for chronic migraine. We describe 2 clinical cases of CH examining the role of Onabotulinum-toxin-A on this form of primary headache. We treated with Onabotulinum-toxin-A two men (46 and 65 years-old) with refractory CH, with a periodicity of 3–4 months, in the muscles of the head and neck following a Blumenfeld treatment paradigm. The first patient has undergone six applications of Onabotulinum-toxin-A (total dosage of 155 U-31 sites) with a follow-up of two years. The second patient has undergone ten applications of Onabotulinum-toxin-A (total dosage between 105 and 195 U-31-39 sites), with a follow-up of three years. Symptoms improvement appeared after the second infiltrative treatment in both case with persistence of effectiveness until seven treatment, with intensity and frequency attack reduction. The first patient reported rare episodes of temporo-mandibular joint tension. The second case showed a total cessation of attacks. Interleukin-1 is a potent prototypical pro-inflammatory cytochine implicated in the pathogenesis of CH, and botulinum toxin inactivate interleukin-1.Onabotulinum-toxin-A can represent a valid alternative prophylactic therapy in CH.